Can preoperative nasal cultures of Staphylococcus aureus predict infectious complications or outcomes following repair of fracture nonunion? - David P. Taormina; Sanjit R. Konda; Frank A. Liporace; Kenneth A. Egol (Elsevier, 2018)
Introduction: Much has been studied with reference to methicillin resistant Staphylococcus aureus (MRSA) and methicillin sensitive S. aureus (MSSA) colonization and associated outcomes and comorbidities. In the area of Orthopedic surgery, literature predominantly comes from the field of arthroplasty. Little is known about outcomes of fracture and Orthopedic trauma patients in the setting of S. aureus colonization. We believe that MRSA/MSSA colonization in and of itself may be a weak marker for generally poor protoplasm, potentially with complex medical history including previous hospitalization or rehab placement. This milieu of risk factors may or may not contribute to poorer outcomes after fracture and fracture nonunion surgery. The purpose of this study is to determine if nasal swabbing for S. aureus (MRSA or MSSA) carriage can predict operative culture, complications, or outcomes following fracture nonunion surgery. Methods: Sixty-two consecutive patients undergoing surgery for fracture nonunion were prospectively followed. Data analyses were performed using grouped MRSA and MSSA carriers (Staphylococcus carriers: SC). Outcomes analyzed included time to healing, need for additional surgery, and persistent nonunion. Results: Twenty-six percent of patients (16/62) were identified as MSSA carriers, an additional 6.5% (4/62) carried MRSA. Follow-up of at least 12-months was obtained on 90% (56/62) of patients. White blood cell counts, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) values did not differ between SCs and non-carriers pre-operatively. Carriers were just as likely as non-carriers to culture positively for any pathogen at the time of surgery. Although SC's were three times as likely as non-carriers to grow S. aureus (15% vs. 5%), this difference did not reach statistical significance (p = 0.3). Post-operative wound complications, antibiotic use, pain at follow-up and progression to healing did not differ between groups. Conclusions: Ultimately, pre-operative nasal swabbing for S. aureus is a simple and non-invasive diagnostic tool with prognostic implications in patients undergoing fracture nonunion surgery. This study found that MRSA and MSSA colonized patients with fracture nonunion of long bones do not have an increased association with positive cultures or a predisposition towards greater post-operative infectious complications. Keywords: MRSA, MSSA, Infection, Nasal carriage, Fracture nonunion